Measuring Internet Service Quality Of E-Commerce Web Sites By Using E-S-Qual In Turkey - Nevin Kortunay (European Scientific Journal, ESJ, 2016)
All firms in the service sector are required to have better service quality in order to accomplish a superior position in competition in the market economy. This need is also valid for firms which are involved in ecommerce. They also need to measure their own service quality to acqure better service quality. The purpose of this study is to review kpe internet service quality of ecommerce web sites in Turkey. There are many methods in the literature which are used to measure internet service quality. E-S-Qual model is one of these methods and it will be used for this survey. This research study shall be carried out by using a structured questionnaire based on E-S-Qual model. The survey shall also attempt to find a relationship between the effects of E-S-Qual dimensions on customer perceived value, e-customer satisfaction, and e-loyalty.